Midazolam in paediatric premedication : the pharmacokinetics, clinical efficacy and ability to modulate behaviour patterns postanaesthesia - Payne, K. A.(Keith Attwood) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1989.